Impact of Short-Term Emission Control Measures on Air Quality in Nanjing During the Jiangsu Development Summit - Zhang, Haoran; Tang, Keqin; Feng, Weihang; Yan, Xintian; Liao, Hong; Li, Nan (Frontiers in Environmental Science, 2021)
This study analyzed the effectiveness of temporary emission control measures on air quality of Nanjing, China during the Jiangsu Development Summit (JDS). We employed a regional chemistry model WRF-Chem to simulate air pollutants in Nanjing and compared the results to surface observations and satellite retrievals. During the JDS, air pollutant emissions from industry and transportation sectors largely decreased by 50-67% due to the short-term emission control measures such as reducing coal combustions, shutting down factories, and partially limiting traffic. Benefiting from the emission control, the simulated concentrations of PM2.5, NO2, SO2, CO and VOCs in Nanjing decreased by 17%, 20%, 20%, 19%, and 15% respectively, consistent with the surface and satellite observations. However, both the observed and simulated O3 increased by 3-48% during the JDS, which was mainly due to the remarkable NOx emission reduction (26%) in the downtown of Nanjing where the O3 production regime was mainly VOC-controlled. In addition, the atmospheric oxidation capacity and further the sulfur oxidation ratio, were facilitated by the elevated O3, which led to variable mitigation efficiencies of different secondary PM2.5 compositions. Our study offers an opportunity for understanding the coordinated control of PM2.5 and O3 in typical city clusters, and can provide implications for future mitigation actions.